Frequency and impact of suboptimal immune recovery on first-line antiretroviral therapy within the International Epidemiologic Databases to Evaluate AIDS in East Africa. (31st July 2016) - Nakanjako, Damalie; Kiragga, Agnes N.; Musick, Beverly S.; Yiannoutsos, Constantin T.; Wools-Kaloustian, Kara; Diero, Lameck; Oyaro, Patrick; Lugina, Emanuel; Ssali, John C.; Kambugu, Andrew; Easterbrook, Philippa
Abstract : Objective: To describe patterns of suboptimal immune recovery (SO-IR) and associated HIV-related-illnesses during the first 5 years following first-line antiretroviral therapy (ART) initiation across seven ART sites in East Africa. Design: Retrospective analysis of data from seven ART clinical sites (three Uganda, two Kenya and two Tanzania). Methods: SO-IR was described by proportions of ART-treated adults with CD4 + cell counts less than 200, less than 350 and less than 500 cells/μl. Kaplan–Meier survival analysis techniques were used to assess predictors of SO-IR, and incident rates of HIV-related illnesses at CD4 + cell counts less than 200, 200–350, 351–499, and >500 cells/μl, respectively. Results: Overall 80 843 adults initiated non-nucleoside reverse transcriptase inhibitor-based first-line ART; 65% were women and median CD4 + cell count was 126 [interquartile range (IQR), 52–202] cells/μl. Cumulative probability of SO-IR <200 cells/μl, <350 cells/μl and <500 cells/μl, after 5 years, was 11, 38 and 63%, respectively. Incidence of HIV-related illnesses was higher among those with CD4 + cell counts less than 200 and 200–350 cells/μl, than those who achieved CD4 counts above these thresholds. The most common events, at CD4 < 200 cells/μl, were pulmonary tuberculosis [incident rate 15.98 (15.47–16.51)/100 person-years at risk (PYAR), oral candidiasis [incident rate 12.5 (12.03–12.94)] and herpes zoster [incident rate 6.30 (5.99–6.64)] events/100 PYAR. With attainment of a CD4 + cell count level 200–350 cells/μl, there was a substantial reduction in events/100 PYAR – by 91% to 1.45 (1.29–1.63) for TB, by 94% to 0.75 (0.64–0.89) for oral candidiasis, by 84% to 0.99 (0.86–1.14) for Herpes Zoster, and by 78% to 1.22 (1.07–1.39) for chronic diarrhea. The incidence of all events decreased further with CD4 counts above these thresholds. Conclusion: Around 40% of adults initiated on ART have suboptimal immune recovery with CD4 counts <350 cells/μl after five years. Such patients will require closer monitoring for both HIV-related and non-HIV-related clinical events.